Aroma profile of Eucalyptus globulus: collected from North West Karnataka, India - Joshi, RK (Scientific World, 2012)
The chemical composition of the essential oil of the leaves of Eucalyptus globulus (Myrtaceae) grown in North West Karnataka, has been analyzed by GC and GC/MS. Forty-eight constituents were identified, accounting 97.93% of the total oil. The major compounds were á-phellandrene (40.31%), á-pinene (13.71%), â-pinene (13.31%), ã-terpinene (9.61%) and 1,8-cineol (4.96%). The oil was rich in monoterpene hydrocarbons (81.14%). Scientific World, Vol. 10, No. 10, July 2012 p89-90 DOI: http://dx.doi.org/10.3126/sw.v10i10.6870